Marasmius vagus (the Wandering Creamsicle), One of Florida’s Most Common Lawn Mushrooms - Sarah Prentice; Matthew E. Smith (EDIS)
Marasmius vagus is one of the most common lawn mushrooms in the state of Florida. The purpose of this publication is to introduce Floridians to this mushroom, provide basic information about its biology, and aid in identification. Written by Sarah Prentice and Matthew E. Smith, and published by the UF/IFAS Plant Pathology Department, February 2024.